The Constellation of Macrovascular Risk Factors in Early Onset T2DM: A Cross-Sectional Study in Xinjiang Province, China - Mingchen Zhang; Jiangfeng Mao; Ablikm Tuerdi; Xiaoyun Zeng; Li Quan; Shan Xiao; Jun Zhu; Hua Yao (Journal of Diabetes Research)
Background. Despite a rapid popular of early onset type 2 diabetes (defined as diagnosis at <40 years old) recently, there is a lack of studies on this population in economically undeveloped area. We aimed to investigate the risk factors of macrovascular complications in the early onset T2DM patients in Xinjiang, China. Methods. A cross-sectional survey of 1736 consecutive patients with T2DM was conducted. Macrovascular complications and risk factors were documented. Another nondiabetic population matched with age and sex was as a control group. Logistic regression analysis was performed to obtain odds ratios (OR) for macrovascular complications in early and late onset T2DM, respectively. Results. The final analysis consisted of 1036 late onset and 219 early onset T2DM patients. The mean HbA1c in the early onset group was higher than that in the late onset group (9.1 ± 2.4% versus 8.3 ± 2.2%, P=0.039) despite a higher proportion of patients in the early onset group receiving insulin treatment (73.1% versus 58.7%, P<0.001). Compared to the control, early onset patients had higher blood pressure and worse lipid profiles (all P<0.01). More than half of the early onset T2DM patients already had macro- and microvascular complications, despite of their young age (39.5 ± 10.8) and short DM duration (6.6 ± 8.0). In the early onset group, women had a ~3-fold hazard of atherosclerotic plaques compared with men (OR 3.22, 95% CI 1.53–6.78). Conclusions. Patients with early onset T2DM have worse glycemic control and higher burden of atherogenic risk factors. The prevalence of macro- and microvascular complications is astonishingly high in these young adults with T2DM. Moreover, young women with T2DM are more susceptible to cardiovascular complications than their male counterpart.